Columbia 1968: the New York Intellectuals’ faculty response to the student sit-ins - Sweeting, Theodore Patrick Abraham (2009)
This dissertation seeks to extrapolate the broader political and intellectual implications of the New York Intellectuals’ responses to the incidents of student protest that occurred on the Columbia University campus in 1968. Firstly three groups who were involved in the incidents are set up; the students, the faculty and the administration. By exploring how their actions influenced the student strikes and resulting media frenzy, the dissertation seeks to demonstrate three distinct political positions which current academia places these factions in. By analysing the New York Intellectuals’ direct responses to the incidents, focusing primarily on the members of the intellectual cadre who were themselves faculty members at Columbia, it then seeks to analyse their political and intellectual inclinations on a subject that was very close to home, both literally and figuratively. The broader personal, political and intellectual opinions of the figures are then drawn out in order to illuminate any shared ground or ruptures in the New York Intellectual group, at a time traditionally seen as heralding the end of their cohesive unit, the end of the liberal consensus and sometimes a beginning of neo-conservative political thought.